Development of STEM-Based Learning Devices on Pythagorean Theorem Materials - Yety Maryanata; Iskandar Wiryokusumo; Ibut Priono Leksono (Pancaran Pendidikan, 2022)
This study aimed to develop STEM-based Mathematics learning devices equipped with STEM-based worksheets. Devices developed based on STEM can make it easier for students to follow the learning process of Mathematics subject that are equipped with clear instructions in working on all the materials and assignments that will be accepted by students. From the results of data analysis and testing on 30 students of class VIII at SMP Negeri 1 Torjun, Sampang Regency, it was found that this research resulted that the product developed was feasible to be used in the learning process of Mathematics subject. In detail, this conclusion explains that the design expert test, material expert test, peer test, and trials to respond to the products were carried out by 5 students, and continued in limited group trials and large group trials, the results always showed an increase after a small revision was made which resulted in a total percentage of 85.3% being obtained from all aspects, so that the product developed on STEM-based learning devices can be socialized and disseminated to teachers and students to be used as a basis for product development in Mathematics subject in the material of Pythagorean Theorem in Class VIII SMP Negeri 1 Torjun, Sampang Regency.